2020
DOI: 10.1038/s41587-020-0555-7
|View full text |Cite
|
Sign up to set email alerts
|

CHANGE-seq reveals genetic and epigenetic effects on CRISPR–Cas9 genome-wide activity

Abstract: Current methods can illuminate the genome-wide activity of CRISPR-Cas9 nucleases, but are not easily scalable to the throughput needed to fully understand the principles that govern Cas9 specificity. Here we describe ‘circularization for high-throughput analysis of nuclease genome-wide effects by sequencing’ (CHANGE-seq), a scalable, automatable tagmentation-based method for measuring the genome-wide activity of Cas9 in vitro . We applied CHANGE-seq to 110 sgRNA targets across 13 therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
227
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(256 citation statements)
references
References 51 publications
(55 reference statements)
7
227
0
Order By: Relevance
“…4G, H thus reports the number of potential off-target sites for each mismatch number for the human and mouse gRNAs. Future implementations of CRISPR mediated B cell engineering in the clinical setting may further require a deep unbiased analysis of off-target cleavage distribution 19 . The ultimate cleavage site in the human IgH J-C intron can then be chosen (Supplementary Data 1) based on it being associated with a minimal off target cleavage profile.…”
Section: Resultsmentioning
confidence: 99%
“…4G, H thus reports the number of potential off-target sites for each mismatch number for the human and mouse gRNAs. Future implementations of CRISPR mediated B cell engineering in the clinical setting may further require a deep unbiased analysis of off-target cleavage distribution 19 . The ultimate cleavage site in the human IgH J-C intron can then be chosen (Supplementary Data 1) based on it being associated with a minimal off target cleavage profile.…”
Section: Resultsmentioning
confidence: 99%
“…Our comprehensive benchmark study of these existing resources provides insightful guidance for off-target effect research in four aspects: (i) The benchmarking of experimental CRISPR off-target detection techniques indicated that the gRNA specificity verifies in different experimental OTS detection techniques, resulting from their different experiment categories, DSBs detecting sensitivities, and even the developing times. A recent study provided a new in vitro genome-wide OTS technique called CHANGE-seq ( 42 ), which was reported to perform better than CIRCLE-seq in sequencing efficacy and parallel experiments. (ii) CRISPR cleavage specificity is heterogeneous in different cell types, resulting from their different genetic and epigenetic information.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the DNA sequence in the cells being investigated can differ substantially from the reference genome used in the computational modeling, potentially resulting in even more false predictions. In recent years, in vitro-based assays [23][24][25][26][27][28] have been developed that allows for experimental detection of Cas9 off-target sites in a particular DNA sample. However, since these methods are based on PCR amplification and short-read sequencing, they have inherent limitations when it comes to detection of Cas9 cleavage in repetitive, low complexity, or AT/GC-rich regions.…”
Section: Introductionmentioning
confidence: 99%